Facile synthesis of a pyrrole-fused dibenzo[a, e]pentalene and its application as a new extended, ladder-type fused aromatic system. Issue 4 (24th November 2014) - Li, Cheng; Liu, Chunming; Li, Yan; Zhu, Xiaozhang; Wang, Zhaohui
Abstract : A novel ladder-type pyrrole-fused dibenzo[ a, e ]pentalene is synthesized via double intermolecular Pd-catalyzed cascade crossover annulations. Abstract : A novel ladder-type pyrrole-fused dibenzo[ a, e ]pentalene, in which two benzo[ a, e ]pentalene units are held coplanar by a nitrogen bridge, is synthesized via double intermolecular Pd-catalyzed cascade crossover annulations. The introduction of a nitrogen bridge not only has a substantial influence on the optoelectronic properties but also improves the processability and stability.